Enzymatic Preparation of Low-Molecular-Weight Laminaria japonica Polysaccharides and Evaluation of Its Effect on Modulating Intestinal Microbiota in High-Fat-Diet-Fed Mice - Fu, Xiaodan; Zhan, Yuming; Li, Nannan; Yu, Dongxing; Gao, Wei; Gu, Ziqiang; Zhu, Lin; Li, Rong; Zhu, Changliang (Frontiers in Bioengineering and Biotechnology, 2022)
Recent studies have shown that seaweed polysaccharides can ameliorate high-fat diet (HFD)-induced metabolic syndromes associated with the regulatory function of gut microbiota. However, kelp, a natural source of seaweed polysaccharides, is highly viscous making it difficult to prepare dietary fiber by simple degradation. Therefore, we developed a novel method of preparing low-molecular-weight polysaccharides from Laminaria japonica by combining high-pressure pre-treatment and composite enzymatic degradation, and evaluated the obesity prevention activity of these polysaccharides. Seaweed L. japonica polysaccharides (SJP) were rapidly utilized by the human fecal microbiota in vitro, resulting in the generation of short-chain fatty acids (SCFAs), specifically acetate and propionate. The in vivo effects of SJP on the intestinal microbiota were also investigated using HFD-fed C57BL/6J mice. SJP reduced weight gain and fat deposition in HFD-fed mice and increased the concentration of total SCFAs, including acetate, propionate, and butyrate in the feces. SJP ameliorated HFD-induced gut microbiota dysbiosis, resulting in increased abundance of Faecalibaculum, Romboutsia, and Clostridium sensu stricto 1 and decreased abundance of Blautia and Lactobacillus. Further, SJP enhanced the abundance of Akkermansia muciniphila in mice provided with HFD and normal chow. Single strain culture experiments also revealed that SJP promoted the growth of A. muciniphila. This study highlights the potential use of SJP, prepared using composite enzymatic degradation (cellulase and recombinant alginate lyase), in preventing obesity and restoring intestinal homeostasis in obese individuals.